2007
DOI: 10.1111/j.1468-1293.2007.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

No association between HIV disease and its treatment and thyroid function

Abstract: The aims of the study were (i) to investigate the prevalence of overt and subclinical thyroid disease in HIV-positive patients in a London teaching hospital; (ii) to determine risk factors associated with the development of thyroid dysfunction, including highly active antiretroviral therapy (HAART) and individual antivirals, and (iii) to determine the occurrence of thyroid dysfunction longitudinally over 3 years. MethodsThe study consisted of retrospective analyses of thyroid function tests (TFT) in HIV-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 13 publications
5
40
0
11
Order By: Relevance
“…Subclinical hypothyroidism is characterized by slightly elevated TSH and normal FT 4 levels. In the present study, 12.82% of patients had these characteristics, which kept this result above the average prevalence among HIV-infected persons of 3.5% to 12.2% (20)(21)(22). This result was elevated with respect to the overall population, for which the prevalence is 4.3% (19).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Subclinical hypothyroidism is characterized by slightly elevated TSH and normal FT 4 levels. In the present study, 12.82% of patients had these characteristics, which kept this result above the average prevalence among HIV-infected persons of 3.5% to 12.2% (20)(21)(22). This result was elevated with respect to the overall population, for which the prevalence is 4.3% (19).…”
Section: Discussionsupporting
confidence: 52%
“…The most common cause of primary hypothyroidism in the population is Hashimoto's thyroiditis, which has a prevalence of 0.3% (18,19). Among HIV-infected individuals, the prevalence of primary hypothyroidism is approximately 2.6% (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…A normal TFT was obtained in 1118 patients (75.5%). 12 Prevalence of overt primary hypothyroidism in the general population and HIV infected individuals from different studies across the globe has been reported to be 0.3% and 0-2.6%, respectively. 1,2,7,10 Similarly, the prevalence of subclinical hypothyroidism has also been reported to be higher in HIV infected individuals as compared to the general population (4.3% versus 3.5-12.2%) in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…11 Madge et al, reported that out of 1565 patients, thirtynine (2.5%) were found to have overt hypothyroidism, and eight (<1%) had overt hyperthyroidism. 12 Sixty-one (4%) had subclinical hypothyroidism, five (<1%) had subclinical hyperthyroidism and 263 (17%) had a nonthyroidal illness. A normal TFT was obtained in 1118 patients (75.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Madge S et al, studied 1565 patients. 7 Out of which, 2.5% had overt hypothyroidism, 4% had subclinical hypothyroidism, normal function was found in 75% of the patients. Varthakavi PK concluded that abnormal thyroid function tests are encountered often in HIV positive individuals.…”
Section: Resultsmentioning
confidence: 99%